KAJIAN KOMUNITAS EKOSISTEM LAMUN DI SEMENANJUNG TARABITAN KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Risandi D Sitaba; Carolus P Paruntu; Billy Theodorus Wagey (JURNAL PESISIR DAN LAUT TROPIS, 2021)
This research was conducted in the waters of Tarabitan Peninsula, West Likupang North Minahasa using quadants transect method. The purpose of this study was to determine the community structure of seagrass found in that waters as initial information for sustainable management seagrass ecosystem . Field observation was conducted to identify the seagrass species, number of individuals/shoots, percent cover for each type of seagrass in those plotting quadrants. The result of this study documented 6 types of seagrass namely, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halophila ovalis and Halodule uninervis. The species composition and distribution of seagrass were varied and was dominated by Thalassia hemprichii was the most dominant seagrass species with a relative density of 55.55%, a relative frequency of 33.67%, 39.92% relative cover, an important value index of 129.03%, a diversity index of 1.30 belonging to this condition, moderate, the uniformity index of 0.72 is classified as high and the dominance index of 0.2 is classified as low. Based on Minister of Environment Decree Republic Indonesia No. 200 of 2004 concerning the status of seagrass beds, the condition of the seagrass beds in the waters of Tarabitan Village is classified as rich / healthy with a cover value of ≥ 60. Keywords : Seagrass Community, Species Composition,  distribution, Tarabitan Peninsula           Penelitian ini dilakukan di perairan Semenanjung Tarabitan Likupang Barat Minahasa Utara dengan menggunakan metode transek kuadran. Tujuan penelitian ini adalah untuk mengetahui struktur komunitas lamun yang terdapat di perairan tersebut sebagai informasi awal untuk pengelolaan lamun secara berkelanjutan. Pengamatan lapangan dilakukan untuk mengidentifikasi jenis lamun, jumlah individu/tegakan, persentase tutupan tiap jenis lamun pada tiap kuadran. Hasil penelitian ini mendokumentasikan 6 jenis lamun yaitu Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halophila ovalis dan Halodule uninervis. Komposisi jenis dan sebaran lamun bervariasi dan didominasi oleh jenis lamun Thalassia hemprichii merupakan jenis lamun yang paling dominan dengan kerapatan relatif 55,55%, frekuensi relatif 33,67%, tutupan relatif 39,92%, indeks nilai penting 129,03%, indeks keanekaragaman 1,30 tergolong dalam kondisi sedang, indeks keseragaman 0,72 tergolong tinggi dan indeks dominansi 0,2 tergolong rendah. Berdasarkan Keputusan Menteri Lingkungan Hidup Nomor 200 Tahun 2004, kondisi padang lamun di perairan Desa Tarabitan tergolong kaya / sehat dengan nilai tutupan ≥ 60.Kata Kunci: Komunitas Lamun, Komposisi Jenis, Distribusi, Semenanjung Tarabitan